Biofilm formation of Enterobacter sakazakii on three different materials of infant feeding tube : a thesis presented in partial fulfillment of the requirements for the degree of Master of Technology in Food Microbiology at Massey University, Palmerston North, New Zealand - Md Zain, Siti Norbaizura Binti (Massey University, 2009)
The aim of this study was to observe biofilm formation by Enterobacter sakazakii (E. Sakazakii) from different clinical, dairy and environmental origins on three infant feeding tubes made of different materials. Infant formula milk was selected as the medium for E. sakazakii growth. Seventeen isolates from different origins were retrieved and tested for purity, using a plating method and biochemical tests to eliminate the non E. sakazakii strains from this study. A method to rapidly and accurately detect viable cells of E. sakazakii on infant feeding tube surfaces using of the BacTrac® 4000 microbiological growth analyser was developed. The sources of errors such as from cleaning, operation and handling procedures were assessed prior to experimental runs. The strength of biofilm formation by different isolates of E. sakazakii on plastic surfaces was scrutinised using a microtiter plate assay. The results from the microtitre plate assay were based on the absorbance at 550 nm of crystal violet stained films and showed that all the clinical isolates were able to attach and form strong biofilms on the plate. Some environmental isolates formed strong or weak biofilms and some did not produce biofilm at all. However, dairy isolates formed both strong and weak biofilms in the microtitre plate when incubated in 10% reconstituted infant formula milk. The further studies were to quantify biofilm formation by three isolates of different origin on three different materials of infant feeding tubes using a batch system. Tubing pieces were incubated with infant formula milk inoculated with E. sakazakii cells at approximately 8 log CFU mL-1 and the biofilm formation was assessed at three time intervals: 4, 12 and 24 hours. Biofilm formation on the tubing by clinical isolates was also observed using epifluorescence microscopy and the scanning electron microscope. E. sakazakii from clinical, dairy and environmental isolates were able to form biofilm on three different materials of infant feeding tubes. The results showed that the initial attachment at 4 h on silicone tubing was low compared with the other two tubes. The scanning electron micrographs showed the surface characteristics of each tubing and the biofilm formation by E. sakazakii clinical isolates after 4, 12 and 24 hours. Silicone tubing appeared to be the best choice for premature babies that need feeding using feeding tubes, as it was slow to become colonised compared with the PVC and polyurethane tubing.
Keywords: Infant formula; Premature babies; Silicone tubing; PVC tubing; Polyurethane tubing; Biofilm; Fields of Research::290000 Engineering and Technology::290100 Industrial Biotechnology and Food Sciences::290105 Other industrial biotechnology